Differential gene analysis during the development of obliterative bronchiolitis in a murine orthotopic lung transplantation model: A comprehensive transcriptome-based analysis - Hata, Atsushi (PLoS One, 2020)
BACKGROUND: Obliterative bronchiolitis (OB) is a known issue during minor histocompatibility antigen (mHA) disparity during lung transplantation. This study evaluated gene expression in a murine orthotropic lung transplantation model using microarray analysis. METHODS: Left lungs from C57BL/10(H-2(b)) donor mice were transplanted into mHA-mismatched C57BL/6(H-2(b)) recipient mice. Three groups (OB, non-OB, and sham controls) were confirmed pathologically and analyzed. Gene expression changes in the lung grafts were determined by microarray and immunohistochemical staining, and genes were verified by quantitative PCR in the lungs and mediastinal lymph nodes (LNs). RESULTS: A total of 1343 genes were upregulated in the OB lungs compared to the sham group. Significant upregulation was observed for genes related to innate, e.g. Tlr2 and CCL3 and adaptive immunity, e.g. H2-ab1 and Il-21. Positive labeling for MHC class II antigen was observed in the bronchial epithelium of OB accompanied with B cells. We found increased Tlr2, Ccl3, H2-ab1, Il-21, Ighg3, Ifng, and Pdcd1 mRNA expression in the OB lung, and increased Il-21, Ighg3, and Pdcd1 expression in the OB LNs. CONCLUSIONS: Adaptive and innate immune reactions were involved in OB after lung transplantation, and genetic examination of related genes could be used for detection of OB.